Pengembangan kurikulum belajar dalam mengatasi Krisis kesenjangan social pada akses kualitas Pendidikan - Nurrohman, Taufik (UHN IGB Sugriwa Denpasar, 2023)
In order to address the educational needs of all of Indonesia's residents, this article discusses social inequities in access and educational quality. The main reasons of socioeconomic disparity in education are things like inadequate educational facilities, a shortage of skilled teachers, and curricula that don't meet the needs of students from varied backgrounds. The Constitution and the National Education System Law were established by the Indonesian government as the cornerstones for establishing an equal educational system and securing every citizen's right to an education. This article emphasizes the significance of creating an inclusive curriculum to suit children' varied intelligences and ensure that all pupils have an equal chance to study. This article's research was conducted using the library, using books and related journal articles as information sources. With the help of this study, an inclusive curriculum will be created and social inequalities in Indonesian education will be addressed. The study's findings are anticipated to positively impact education quality and the development of an inclusive and equitable educational system. The concept of social inequality in education, the function of curriculum in addressing social inequality, and best practices in curriculum development are also discussed in this article. A thorough understanding of social inequalities in education would enable the creation of a more equitable educational system and the provision of equal access for all people.